MENCERMATI IDEOLOGI FIKIH POLITIK GERAKAN FUNDAMENTALISME IKHWAN AL MUSLIMIN DI MESIR - Roibin, Roibin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
The paper discusses the ideology of fundamentalism on political fiqh. Their idea of ‘total Islam’ emerges problematic situation as the concept they build has not yet faced theoretical and practical construction. This is in line with the idea they have, historical-philology, a hint of paragidm which trying to have religious comprehension structurally, textually, and literally. Since its establishment in 1981, Ikhwan community has conducted many political activities. All activities are intended to reach the vision and mission of the organization, even, by conducting an extreme way that is executing the leader who does not response and accomodate their belief, syari’at Islam. This situation leads to a point of view that their movement is successful and fail in two different sides. They successfully defend the consistency to build the religious proselytizing activities. On the other hand, they cannot have any support from the leader to accommodate their activities.